EDUKASI PEMBERIAN TES FUKUDA UNTUK MENGETAHUI GANGGUAN KESEIMBANGAN PADA LANSIA DI KOMPLEK BTN CIERENG SUBANG - Ika Rahman; Fitriani Libiyana Zane; BathrixYolanda Selvia lena; Ersa Rezqi Amelia (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
This service activity is in the form of counseling related to balance in the elderly to find out balance disorders in the elderly. This activity was carried out at the Ciereng BTN Complex located in Subang. The results of this activity are patients with balance disorders, aged over 52 years and over, as many as 10 people with balance disorders on average are women with balance disorders. Constraints faced in the balance disorder test are more common in women than men. Through the Fukuda test they will find out if they have balance disorders, the Fukuda test is considered abnormal if the deviation to one side is more than 30° and or shifts more than 1 meter. The purpose of the balance test in the form of a Fukuda test is to determine the risk of the elderly experiencing balance disorders. It is hoped that the elderly after knowing the results of this Fukuda test can maintain a healthy lifestyle and reduce activities that can worsen balance disorders. The results of this activity the surrounding community stated that the activities carried out were very beneficial for them and quite helpful in knowing the risk of falling.Keywords: Fukuda, Body Balance, Elderly.